(untitled) (Rudarsko-geološko-naftni zbornik, 2024)
Selecting a mining method is an essential step in the initial phases of mining. The selection of an inappropriate mining method can have consequences, such as the potential loss of a portion of the ore deposit. Sometimes, changing the mining method can result in high costs that render the entire project economically unfeasible. For the past two decades, qualitative patterns and numerical scoring have been replaced by multi-criteria decision-making methods. In this study, the Simultaneous Evaluation of Criteria and Alternatives (SECA) multi-criteria decision analysis method was introduced for the first time in the selection of mining methods. The SECA was used to select the mining method in two ore bodies: Gol-E-Gohar No. 3 Iron ore and Chahar-Gonbad Copper ore. The final ranking compared with the results obtained from the fuzzy TOPSIS decision-making method. The satisfactory results indicated that the open-pit method was selected as the appropriate approach for both cases. The SECA method has lower computational complexity because it does not require the use of weight vectors as inputs. However, it does require a precise decision matrix. This method can be considered the foundation of artificial intelligence for selecting a mining method.